Quantitative chest computed tomography in chronic obstructive pulmonary disease: assessing the role of emphysema severity and its correlation with clinical characteristics, lung function, and plasma levels of VEGF and IL-1β - Cong Nguyen Hai; Thanh Bui Duc; The Nguyen Minh; Loi Trinh Duc; Thang Tran Quyet (Therapeutic Advances in Respiratory Disease)
Background: Quantitative computed tomography has emerged as a crucial tool for assessing the severity of emphysema in chronic obstructive pulmonary disease (COPD) patients. Vascular endothelial growth factor (VEGF) levels are significantly elevated in patients with chronic bronchitis but reduced in those with emphysema. Chronic inflammation is a key factor in the pathogenesis and progression of COPD, with cytokines such as Interleukin-1 beta playing a significant role. Objective: This study aimed to evaluate the characteristics of emphysema in patients with COPD using quantitative computed tomography (QCT) and to investigate the relationship between the extent of emphysema, clinical phenotypes, lung function, and plasma concentrations of VEGF and IL-1β in COPD patients. Design: A prospective cross-sectional study was conducted on 30 male patients with stable COPD at Military Hospital 175. Methods: The emphysema index (EI) was quantified using QCT of the chest and categorized into levels from 0 to 4. Data on acute exacerbation frequency, CAT scores, mMRC, pulmonary function indices, arterial blood gas measurements, and plasma concentrations of VEGF and IL-1β were collected and analyzed to determine their relationship with EI. Results: The study found an average EI of 12.8% ± 11.64%, with 96.7% of patients exhibiting a bronchitis-dominant phenotype. The severity of airflow obstruction, PaCO 2 levels, mMRC scores, and the number of exacerbations per year increased with the degree of emphysema. Conversely, FEV1% and the FEV1/FVC ratio significantly decreased with increasing emphysema severity. Plasma VEGF concentration was inversely correlated with the EI. In GOLD 3 and 4 stages, plasma VEGF levels decreased in proportion to emphysema severity, indicating that more advanced emphysema was associated with a more rapid decline in VEGF concentrations. Notably, when emphysema exceeded 25%, a significant reduction in both VEGF and IL-1β concentrations was observed. Conclusion: The EI determined by QCT is a valuable tool for identifying COPD phenotypes and assessing disease severity. It can also provide insights into the prognosis regarding the risk of exacerbations, clinical symptom burden, and lung function decline. The significant inverse correlation between plasma VEGF concentration and EI indicates that decreased VEGF levels may be a crucial factor in the pathogenesis of emphysema, suggesting a potential target for research on “treatable” factors in COPD management. Trial registration: The study was approved by an independent ethics committee (Ethics Committee of Military Hospital 175, No. 003/QĐ-IRB-VN01.055) and conducted in accordance with the Declaration of Helsinki and Guidelines for Good Clinical Practice.